2016
DOI: 10.1371/journal.pone.0167095
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum Transcriptome of Mice Bred for High Voluntary Activity Offers Insights into Locomotor Control and Reward-Dependent Behaviors

Abstract: The role of the cerebellum in motivation and addictive behaviors is less understood than that in control and coordination of movements. High running can be a self-rewarding behavior exhibiting addictive properties. Changes in the cerebellum transcriptional networks of mice from a line selectively bred for High voluntary running (H) were profiled relative to an unselected Control (C) line. The environmental modulation of these changes was assessed both in activity environments corresponding to 7 days of Free (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 124 publications
0
22
0
Order By: Relevance
“…In complementary studies, High Runner lines of mice have been selected for high levels of daily wheel running, and nonselected controls have been maintained for many years (reviewed in). Although these animals have not been tested in the context of addictive drugs, which is an important area for future research, transcriptional profiling revealed differential gene expression patterns in neuronal networks also implicated in addiction, including differences in Drd2 expression …”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…In complementary studies, High Runner lines of mice have been selected for high levels of daily wheel running, and nonselected controls have been maintained for many years (reviewed in). Although these animals have not been tested in the context of addictive drugs, which is an important area for future research, transcriptional profiling revealed differential gene expression patterns in neuronal networks also implicated in addiction, including differences in Drd2 expression …”
Section: Role Of Genetics In Auds and Exercisementioning
confidence: 99%
“…In complementary studies, High Runner lines of mice have been selected for high levels of daily wheel running, and nonselected controls have been maintained for many years (reviewed in103 ). Although these animals have not been tested in the context of addictive drugs, which is an important area for future research, transcriptional profiling revealed differential gene expression patterns in neuronal networks also implicated in addiction, including differences in Drd2 expression 104. Because alcohol and exercise both activate the mesolimbic dopaminergic reward pathway,11,66,88 it can be hypothesized that greater alcohol consuming strains of mice will run farther distances than low or moderate consuming strain of mice.…”
mentioning
confidence: 99%
“…Supplementary Table 2 ). Its function in muscle is largely unknown, but differential expression has been found in rodent cerebellum and spinal cord with exercise (Caetano-Anollés et al, 2016;Perreau et al, 2005) . ID3 is a transcriptional regulator that inhibits skeletal muscle differentiation and promotes muscle precursor cells proliferation (Baas et al, 2012;Liu et al, 2002;Wu and Lim, 2005) .…”
Section: Long-term Training Induces Extracellular Matrix Reorganizatimentioning
confidence: 99%
“…Mouse lines selectively bred for high voluntary wheel-running behavior have been a helpful model for uncovering the neurological basis of motor learning and adaptation, increased motivation of physical activity, and reward-dependent behaviors [ 2 , 5 , 6 ]. Significant behavioral and physiological differences can be identified between lines selected for high voluntary running and non-selected control lines [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the expected association with reward-dependent pathways, we reported differential expression between the striatum of the high running and control lines of genes coding for members of the dopamine signaling pathway, including the neurotransmitters glutamate and GABA and the neuromodulator serotonin [ 6 ]. A different set of genes associated with locomotor control, reward-dependent behaviors and dopamine processes, including dopamine receptor D1 and muscarinic acetylcholine receptor M1 were differentially expressed between the cerebellum of the high running and control lines [ 8 ]. A more complete understanding of the complementary role of the striatum and cerebellum on the motivation to exercise in particular, and for reward-dependent behaviors in general necessitates the simultaneous analysis of transcriptome between high running and control lines across brain regions.…”
Section: Introductionmentioning
confidence: 99%